"Broken Hearted" and "Crushed in Spirit": Metaphors and Emotions in Psalm 34, 19. Issue 1 (2nd January 2016) - Eder, Sigrid
Abstract: In the Old Testament, the book of psalms stands out because of its vast and rich imagery and vivid metaphorical language. Deep human experiences and a wide range of human emotions in its heights and depths can be discovered there. The metaphorical language in the Old Testament, particularly in the psalms, is often linked with emotions. This paper centres on emotions within the metaphor discourse and aims to contribute to two fields of research: firstly, the field of metaphor analysis in the psalms and secondly, the area of the Studies of Emotions by using Ps 34, 19 as an example. After presenting some core theoretical concepts regarding the study of metaphors and emotions, the analysis of the form and content of Ps 34 as well as the "broken hearted" and "crushed in spirit" in Ps 34, 19 will be carried out. The results of the analysis shed new light on the well-known verbal images of the "broken hearted" and "crushed in spirit."